REFINING ASAP CAIR KULIT DURIAN (Durio zibhetinus) HASIL PIROLISIS DENGAN DESTILASI SEDERHANA - Dhani Aryanto; Muhammad Rusdi (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2021)
This study aims to determine the characteristics of pyrolysis durian skin smoke, determine the characteristics of durian skin liquid smoke, and determine the yield of durian skin smoke after distillation. Liquid smoke is obtained from the pyrolysis of soft wood and hard wood, one of which is durian skin, durian skin can be used as a raw material in the manufacture of liquid smoke, Besides durian skin contains cellulose, hemicellulose and lignin compounds which are chemicals that form components of liquid smoke. One way to obtain the desired organoleptic properties is by distillation treatment, so it is hoped that the distillation method can produce higher quality liquid smoke as a preservative that is cheap and safe for health. Parameter values ​​of refractive index and pH of durian peel liquid smoke Pyrolysis results are greater than after distillation, except for acetic acid which is smaller. The refractive index value is 1,3572, the pH value is 4,901, and the acetic acid value is 6,172 N. The refractive index and pH values ​​of the distillated durian skin liquid smoke are smaller than those of pyrolysis, except that the acetic acid value is greater. The average value of the refractive index is 1,23467-1,34800, the pH value is 3,44067-2,51600, and the value of acetic acid is 7,37533-7,97600 N. The effect of temperature and distillation time affects the yield value of the resulting liquid smoke. The temperature and time of distillation affect the value of the volume of the distillation result. The higher the distillation temperature and time, the greater the yield. The best treatment is temperature 3 (150oC) and time 3 (90 minutes) of 84.66%.